A digital ecosystem framework for prospective and strategic scenario planning - Quesang, Winston Wagner Tiu (University of the Philippines Diliman, Technology Management Center, 2012)
Technology innovation and improvement is inevitable. But why not all technologies are successfully commercialized? And, why even the not so best technologies out there survive? Recognizing Everett Roger's Technology Adoption Life Cycle, where we understand each stage of technology consumer adoption to gain market control, Geoffrey Moore reiterates that the model has a chasm. He states that not all products and technologies went into the market can successful cross this chasm to penetrate the mainstream market. Here, we also acknowledge that the common issues in high-tech markets is the product adoption risk due to consumers' fears, uncertainties, and doubts (FUD Factor), its high competitive volatility, technological uncertainties and market uncertainties. With the given problems in the high-tech industry, the researcher tried to understand the common problems in bridging the gap between the technology and the market, and was able to formulate a strategic framework, to aid technology managers, product development managers, strategist, innovators, decision makers and technopreneurs in their strategic scenario planning process. To come up with a strategic Digital Ecosystem Framework, the researcher combined three innovation strategies, composed of the (1) Digital, (2) Business and (3) Marketing Innovation Strategies. This study also explains and shows on how the strategic framework works in the current high tech market. From market players, all the way down to a tech start up, who wishes to beef up its digital ecosystem strategy. This study also explains and shows on how the strategic framework works in the current high-tech market. From market players, all the way down to a tech start-up, who wishes to beef-up its digital ecosystem strategy.